2022
DOI: 10.1039/d1ra07888g
|View full text |Cite
|
Sign up to set email alerts
|

Wearable microfluidic-based e-skin sweat sensors

Abstract: Electronic skins are soft wearable devices that emulate attributes of human skin and act as a human–machine interface for early prediction and real-time monitoring of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 125 publications
(194 reference statements)
0
29
0
Order By: Relevance
“…This innovative sticker technology and the emergence of new wearable gadgets and sensors give them hope. [3][4][5][6][7][8][9][10]…”
Section: Smart Stickers and Their Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…This innovative sticker technology and the emergence of new wearable gadgets and sensors give them hope. [3][4][5][6][7][8][9][10]…”
Section: Smart Stickers and Their Operationmentioning
confidence: 99%
“…[1][2][3][4][5] Although there are schemes for rapid diagnosis, however, smart, and non-invasive techniques are very few. [5][6][7][8][9][10][11][12][13] This short communication deals with a smart sticker which can detect CF at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a push toward the development of wearable sensors that could enable real-time measurements of sweat chloride concentration. 51 52 These new techniques appear to be reliable when used during moderate exercise and may provide an indirect biomarker for assessing response to CFTR modulators over time and the need for electrolyte replacement during exertion and heat exposure 53 54 .…”
Section: Wearable Devicesmentioning
confidence: 99%
“…A growing number of research studies that have been reported on analyzing various sweat biomarkers for use in a broad range of clinical diagnostic purposes, including health concerns, nutritional imbalance, drug abuse, and many more [ 1 , 2 , 3 , 4 ], have seen a ten-fold rise in this field, as shown in Figure 1 . However, there are still gaps in the structured content on related SSD applications based on the current existing review articles, such as insufficient information about a few sweat biomarkers, especially hormones, drugs, nicotine, and vitamin C, and inadequate detailed explanation of the respective application concepts related to these biomarkers and a lack of a fundamental response mechanism of chemical sensors that enable users to understand the process of the target analyte’s detection for various sweat compositions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Despite these limitations, the existing reviews seemed to disregard addressing issues such as an analysis effect formation mixing new and old sweat samples, which can be a daunting challenge for acquiring a high precision in sweat analysis.…”
Section: Introductionmentioning
confidence: 99%